Preservação e o acesso aos microfilmes do acervo do centro de Registro e Indicadores Acadêmicos da Universidade Federal do Pará - SILVA, Bruna Marques da (2022)
Analysis of techniques of preservation of microfilms in the collection of the Center for Registration and Academic Indicators (CIAC) of the Federal University of Pará, discussing the importance of this to guarantee access to information and making possible the presentation of improvements in microfilm collection. For the preparation of this research, a bibliographic survey of articles, books and manuals was carried out and, based on a case study, the application of interviews and questionnaires to the employees that deal with the collection in CIAC. The research carried out a study on the concept of microfilming, methods and practices of preservation of microfilms and the microfilm collection in the CIAC. The research, observing the practices of preservation in the place, realized that the CIAC presents some fragilities of packaging and handling of this material, where solutions were suggested for these problems.